2021
DOI: 10.1002/smll.202106048
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Assembly of Colloids and Eumelanin Nanoparticles in Droplets for Structural Pigments with High Saturation

Abstract: Colloidal crystals have been used to develop structural colors. However, incoherent scattering causes the colors to turn whitish, reducing the color saturation. To overcome the problem, light‐absorbing additives have been incorporated. Although various additives have been used, most of them are not compatible with a direct co‐assembly with common colloids in aqueous suspensions. Here, the authors suggest eumelanin nanoparticles as a new additive to enhance the color chroma. Eumelanin nanoparticles are synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…33 Water-dispersible carbon black nanoparticles and eumelanin nanoparticles have been respectively employed to suppress the whitening over the entire visible range. 34,35 The use of a proper additive selectively reduces the scattering in off-resonant wavelengths and significantly enhances the color saturation as long as it does not disturb the colloidal crystallization, as shown in Fig. 1e.…”
Section: Colloidal Self-assembly In Emulsion Dropsmentioning
confidence: 99%
“…33 Water-dispersible carbon black nanoparticles and eumelanin nanoparticles have been respectively employed to suppress the whitening over the entire visible range. 34,35 The use of a proper additive selectively reduces the scattering in off-resonant wavelengths and significantly enhances the color saturation as long as it does not disturb the colloidal crystallization, as shown in Fig. 1e.…”
Section: Colloidal Self-assembly In Emulsion Dropsmentioning
confidence: 99%
“…13−21 To enhance color purity and suppress white appearance, broadband light absorbers are often incorporated inside PBs. 19,22 PB-based inks, however, have never been tested before for inkjet printing applications. The lack of studies is likely related to standard inkjet-printing technology's substantial pigment size limitations.…”
Section: Introductionmentioning
confidence: 99%
“…One can suspend the PBs in a solvent phase and then use the obtained colored ink for practical applications. Commonly, PBs with sizes in the tens of micrometer range are employed. To enhance color purity and suppress white appearance, broadband light absorbers are often incorporated inside PBs. , …”
Section: Introductionmentioning
confidence: 99%
“…Inspired by these elegant examples in nature, many studies have explored light absorption materials to prepare photonic materials with enhanced brightness and biomimetic metallic effects. In the cases of CNC-based chiral photonic films, Droguet et al recently achieved certain metallic effects in the coloration of partially carbonized CNC films by heating the neat films at very high temperature . However, further carbonation leaded to black materials without any colors and fragmentation of the CNC films.…”
Section: Introductionmentioning
confidence: 99%
“…However, further carbonation leaded to black materials without any colors and fragmentation of the CNC films. Instead of such a specific method, incorporation of light absorption materials into photonic materials is a more general strategy. By doping thermally reduced graphene (TRG) into CNC films, Nan et al imparted certain metallic effects into their hybrid CNC/TRG films . Wang et al recently reported cellulose films with vivid colors by preparing the pristine CNC-based photonic films at first and then infiltrated the films with the light adsorption materials of polydopamine (PDA) .…”
Section: Introductionmentioning
confidence: 99%